Morphological characterization and cutting moments of the people of natural and cultivated minthostachys muña mollis (kunth.) griseb. for obtaining essential oils in the micro of Higueras - Maquera Lupaca, David (2009)
This study was carried out in the town of Mitotambo, district of Quichki, province of Huánuo, at 2 800 m altitude, the objective was to describe the morphologic characteristics about  the natural population and cultivated of muña Minthostachys mollis (Kunth.) Griseb., to evaluate the frequency of cut in muña and the effect in the Essentials oils. To be made a descriptor of muña, this has 25 characters and 91 states with dates or variables what describe the organs different of muña. Thirteen were the accessions of wild muña registered and 97 accessions of culture cultivated; these were associated in 6 and 49 groups respectably, to 1.30 and 1.0 of genetics distances; to stand out the characteristics in relation to major percentage of every one. The farmer woman, know the variability about the muñas as white muña and black muña that existed in the zone. The moment appropriated of cut is the start of flower, with major production of fresh leafs. The production of essential oils in the different states phenologic of muña, was similar.